Corporate board, diversification strategies, and the value of diversified listed companies: the moderating effect of managers' wealth maximization on diversification value - Salisu, Umar (2020)
Keeping in view the important role of Malaysian corporate sector in the country’s growth and development, and proliferation of diversified companies, this study was conducted on Public Listed Companies (PLCs) on Bursa Malaysia’s Main Market. This study examines the relationship between corporate board, diversification, the value of diversified listed companies in Malaysia, with the moderating effect of managers’ wealth maximization on diversification strategies and value. Secondary data was obtained mainly from the companies’ annual reports published. This study utilised sample of 490 PLCs, and employed multiple regression techniques to analyse data and draw conclusions. Findings of the study reveals that board independence and risk management committee have positive impact on diversification value. Meanwhile board size, audit independence, audit committee size and tenure of independent directors have negative impact on the diversification value. Furthermore, the findings show that related diversification strategy positively affects diversification value, whereas unrelated diversification strategy has a negative impact on diversification value. Managers’ wealth maximization positively moderates the relationship between related diversification strategy and diversification value. However, managers’ wealth maximization shows a negative moderation relationship between unrelated diversification strategy and diversification value. Related diversifiers seem to outperform unrelated diversifiers on all the three diversification value dimensions (sales, ebit & asset). The findings supports the agency and resource dependency theories on the view that enhanced corporate governance practices could contribute towards increasing diversification value. In addition, the findings may also assist corporate managers to get rid of the dilemma on their choice of the best and most profitable diversification strategies. Generally, this study provides additional insights to policy makers and regulators towards improving corporate governance policies in the future. It may also help to increase understanding the relationship between corporate governance practices, diversification strategies and firm value.